The unintended consequences of employer credit check bans on labor and credit markets - Kristle Cortés; Andrew Glover; Murat Tasci (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
Lenders have traditionally used credit reports to measure a borrower's default risk, but credit agencies also market reports to employers for use in hiring. Since the onset of the Great Recession, eleven state legislatures have restricted the use of credit reports in the labor market. We document that county-level unemployment rose faster in states that restricted employer credit checks and counties with more sub-prime citizens experienced larger increases in the unemployment rate than average. Using data from individual credit reports, we find that access to credit declines and delinquencies increase significantly after the state-level policy changes, especially for subprime borrowers.
Keywords: 330